2010
DOI: 10.1111/j.1600-6143.2010.03211.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Recipient Race on the Outcome of Simultaneous Pancreas and Kidney Transplantation

Abstract: Racial differences on the outcome of simultaneous pancreas and kidney (SPK) transplantation have not been well studied. We compared mortality and graft survival of African Americans (AA) recipients to other racial/ethnic groups (non-AA) using the national data. We studied a total of 6585 adult SPK transplants performed in the United States between January 1, 2000 and December 31, 2007. We performed multivariate logistic regression analyses to determine risk factors associated with early graft failure and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
0
21
2
Order By: Relevance
“…The significant decrease in patient and graft survival in African American recipients of race-matched pancreas transplants is particularly notable, as the 7.1% decrease in patient survival at 5 years (CI À2.4 to À11.7%, P-value 0.003) and 9.5% decrease in graft survival at 5 years (CI À3.4 to À15.6%, P-value < 0.001) were the greatest differences noted in any race category or organ system. Few prior studies have looked at the impact of racial factors on pancreas transplant outcomes [10], but as with most organ systems, organ scarcity, and annual transplant volume limit the utility of this finding to warrant consideration of race-matching in allocation of pancreas grafts. While the worsening of outcomes in race-matched African American recipients is surprising, it is not unprecedented.…”
Section: Discussionmentioning
confidence: 99%
“…The significant decrease in patient and graft survival in African American recipients of race-matched pancreas transplants is particularly notable, as the 7.1% decrease in patient survival at 5 years (CI À2.4 to À11.7%, P-value 0.003) and 9.5% decrease in graft survival at 5 years (CI À3.4 to À15.6%, P-value < 0.001) were the greatest differences noted in any race category or organ system. Few prior studies have looked at the impact of racial factors on pancreas transplant outcomes [10], but as with most organ systems, organ scarcity, and annual transplant volume limit the utility of this finding to warrant consideration of race-matching in allocation of pancreas grafts. While the worsening of outcomes in race-matched African American recipients is surprising, it is not unprecedented.…”
Section: Discussionmentioning
confidence: 99%
“…Rogers et al 9 and Luan et al 10 both reported that AA recipients had worse pancreatic graft survival than other racial recipients at 1, 3, and 5 years. Similarly, Danovitch et al 20 revealed that AA recipients experienced higher rate of pancreatic graft failure than Caucasian recipients.…”
Section: Discussionmentioning
confidence: 99%
“…in 1966, there have been numerous advances in the surgical technique and immunosuppressive regimens, allowing for better pancreatic graft and patient survival 7 . Despite these innovations in PTx, racial differences are known to exist that affect the outcomes, as not all racial recipients or donors have the same survival benefit 4,8–12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series, primary thrombosis accounted for 12 of 28 (50%) death-censored gra failures and was responsible for 11/14 pancreatic gras (78.6%) lost within a month of transplantation. Large series have documented thrombosis to be responsible for the majority of technical failures and early gra loss [4,23]. Factors that have been shown to predispose to gra thrombosis include recipient obesity, preservation time, and nontraumatic causes of donor death [4,24].…”
Section: Discussionmentioning
confidence: 99%